Thermal performance of desiccant-integrated and conventional Maisotsenko cooling systems in a high humidity tropical climate - Haiqal Irfansyah; Sarwo Edhy Sofyan; Razali Razali (Politeknik Negeri Lhokseumawe, 2026)
Tropical regions are characterized by a distinctive climate, marked by consistently high temperatures and significant humidity throughout the year. These conditions necessitate the use of cooling systems to ensure thermal comfort. Previous studies have shown that the Maisotsenko cooling system experiences a decline in efficiency when operating in high-humidity environments. Conversely, desiccant systems are effective in reducing air humidity. This study aims to design and experimentally evaluate the performance of a Maisotsenko cooling system under high-humidity tropical conditions, as well as the effect of integrating a desiccant system on its cooling efficiency. The experiments were conducted using a laboratory-scale fabricated test rig, consisting of a Maisotsenko cooling unit with a channel length of 180 mm and a desiccant unit with a channel length of 140 mm. Tests were performed using a standalone Maisotsenko system and a combined Maisotsenko-desiccant system. Air velocity was varied at 3 m/s, 4 m/s, and 5 m/s, with an air ratio of 0.5. The results showed that for the Maisotsenko system without a desiccant, the best cooling performance under high humidity conditions occurred at an air velocity of 3 m/s, achieving a temperature reduction of 1.7°C, a heat transfer rate of 1.4 W, a dew point temperature effectiveness of 27.5%, and a wet-bulb temperature effectiveness of 37.3%. In contrast, the combined system with a desiccant at 3 m/s provided enhanced temperature reduction, dew point effectiveness, and wet-bulb effectiveness of 2°C, 32.4%, and 43.8%, respectively. The highest heat transfer rate, however, was recorded at 5 m/s with a value of 1.9 W. The integration of a desiccant system significantly improved the cooling performance of the Maisotsenko system in terms of temperature reduction, heat transfer rate, and cooling efficiency. At air velocities of 3 m/s, 4 m/s, and 5 m/s, the cooling performance increased by 17.6%, 78.9%, and 366.7%, respectively.